Correction to: The mechanism of electroacupuncture for depression on basic research: a systematic review - Xuke Han; Yang Gao; Xuan Yin; Zhangjin Zhang; Lixing Lao; Qiu Chen; Shifen Xu (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.